2016
DOI: 10.1089/dna.2015.2908
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Y Box Binding Protein 1 C-Terminal Domain in Vascular Endothelial Cell Proliferation, Apoptosis, and Angiogenesis

Abstract: Different domains of the multifunctional transcription factor Y-box binding protein 1 (YB1) regulate proliferation, differentiation, and apoptosis by transactivating or repressing the promoters of various genes. Here we report that the C-terminal domain of YB1 (YB1 CTD) is involved in endothelial cell proliferation, apoptosis, and tube formation. The oligo pull-down assays demonstrated that YB1 directly binds double-stranded GC box sequences in endothelial cells through the 125-220 amino acids. Adenovirus expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Consistent with our findings, p21, a potent cyclin-dependent kinase inhibitor, plays a role similar to that of GAS5 and functions as a regulator of cell cycle progression at the G1 and S phases 35. Moreover, previous studies have identified the regulation of p21 expression and subsequent G1 phase arrest by the YBX1 protein 20, 37. p21 has been shown to be a functional target of GAS5 in ovarian cancer cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, p21, a potent cyclin-dependent kinase inhibitor, plays a role similar to that of GAS5 and functions as a regulator of cell cycle progression at the G1 and S phases 35. Moreover, previous studies have identified the regulation of p21 expression and subsequent G1 phase arrest by the YBX1 protein 20, 37. p21 has been shown to be a functional target of GAS5 in ovarian cancer cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…30 In addition, Wang found that YBX1 overexpression also increased Bax, decreased Bcl-2 expression, and induced apoptosis in vascular endothelial cells. 31 In accordance with the previous studies above, our study showed that YBX1 was a negative regulator of apoptosis in chordoma.…”
Section: Ybx1 Promotes Chordoma Tumor Growth In Vivosupporting
confidence: 92%
“…Vascular endothelial growth factor (VEGF) in conditioned media was quantified using VEGF ELISA Kits (Neobioscience Technology, China). To investigate the effect of the conditioned media on the angiogenic activity of EA.hy926 cells in vitro , a tube formation assay was performed according to the protocol described previously (21). EA.hy926 cells were seeded into a 24-well plate pre-coated with 100 μL of 10 mg/mL chilled Matrigel (Corning, Bedford, MA) at a density of 1 × 10 5 cells/well in 0.5 mL of culture medium.…”
Section: Methodsmentioning
confidence: 99%